2022
DOI: 10.1002/adfm.202200333
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Valence Metal Single Atoms on Graphdiyne Promotes Electrochemical Nitrogen Reduction via M‐to‐N2 π‐Backdonation

Abstract: The M‐to‐N2 π‐backdonation weakens the triple bond of N2 and shall promote the sluggish electrochemical nitrogen reduction reaction (ENRR). By using weak σ‐ and π‐donating graphdiyne (GDY) as a supporting material, herein, a versatile approach is described to stabilize low‐valence metal single atoms (SA) on GDY (M SA/GDY; M = Cr, Mo, W, Mn, and Re). Under the rigorous ENRR protocol, an activity trend of Re SA/GDY > Mo SA/GDY > Cr SA/GDY > W SA/GDY >> Mn SA/GDY (no activity) is delivered. Theoretical calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 49 publications
0
51
0
Order By: Relevance
“…Duan and co-workers experimentally reported that steric confinement-induced dense Rh single sites (Rh@GDY) achieve enhanced eNRR activity, and DFT calculations indicated a U L of −0.86 V for eNRR on it . Also, the same research group experimentally revealed an activity trend of Re@GDY > Mo@GDY > Cr@GDY > W@GDY ≫ Mn@GDY for eNRR, while the calculated U L from DFT was −0.83 V on Re@GDY . In addition, Li and co-workers reported that Mo single-site supported on GDY (Mo@GDY) is an efficient eNRR catalyst with a joint experimental and theoretical study .…”
Section: Computation-assisted Catalyst Design For Enrrmentioning
confidence: 95%
See 1 more Smart Citation
“…Duan and co-workers experimentally reported that steric confinement-induced dense Rh single sites (Rh@GDY) achieve enhanced eNRR activity, and DFT calculations indicated a U L of −0.86 V for eNRR on it . Also, the same research group experimentally revealed an activity trend of Re@GDY > Mo@GDY > Cr@GDY > W@GDY ≫ Mn@GDY for eNRR, while the calculated U L from DFT was −0.83 V on Re@GDY . In addition, Li and co-workers reported that Mo single-site supported on GDY (Mo@GDY) is an efficient eNRR catalyst with a joint experimental and theoretical study .…”
Section: Computation-assisted Catalyst Design For Enrrmentioning
confidence: 95%
“…129 Also, the same research group experimentally revealed an activity trend of Re@GDY > Mo@GDY > Cr@GDY > W@GDY ≫ Mn@GDY for eNRR, while the calculated U L from DFT was −0.83 V on Re@ GDY. 159 In addition, Li and co-workers reported that Mo single-site supported on GDY (Mo@GDY) is an efficient eNRR catalyst with a joint experimental and theoretical study. 464 Also, Zhai et al theoretically screened a series of TM single sites (Sc, Cr, Mn, Fe, Co, Ni, Cu, Zn, Mo, Ru, Rh, Pd, and Ag) supported GDY for eNRR, where the Mo@GDY is predicted to be a promising catalyst (U L = −0.33 V following the distal pathway) with high stability and high conductivity.…”
Section: Dmentioning
confidence: 99%
“…In the present work, the computed adsorption Gibbs free energy of N 2 is −0.95 eV, and the first protonation step has a Gibbs free energy change of 0.97 eV, in good agreement with the previous study. Moreover, Mo 1 / GDY has been synthesized successfully and proved to be a promising eNRR catalyst. , It is noted that the electron configuration of the early transition metal element Mo is [Kr]­4d 5 5s, with half-full 4 d and 5 s orbitals. The Mo center in Mo 1 /GDY adopts d 2 sp hybridization, which is coordinated by four C atoms in Mo-C 4 moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, our group reported a universal and straightforward method for synthesizing low-valence single atoms on GDY (referred to M SA/GDY; M = Cr, W, Mo, Re, Mn), aiming at maximizing the M-to-N 2 π-backdonation. 85 As shown in Figure 9a, the M SA/GDY catalysts were synthesized by in situ coordination of the relevant metal carbonyl precursors [M(CO) 6-x Cl x ] (x = 0, M = Cr, Mo, and W; x = 1, M = Re and Mn) with the HEB monomer during the Glasercoupling process on the Cu foil. The isolated single-metal atoms can be clearly observed as bright spots in the HAADF-STEM images (Figure 9b).…”
Section: Gdy-based Single-atoms Catalystsmentioning
confidence: 99%